Spatial, temporal, and kinetic variables during the early acceleration phase of sprinting - Thone, A. L.; Frisk, H. L.; Jensen, R. L.; Ebben, W. P. (ISBS Proceedings Archive (Michigan), 2020)
This study evaluated the relationships between spatial, temporal, and kinetic variables and velocity during the early acceleration phase of sprinting. Ten women and ten men performed sprints across two force platforms. Pearson`s and partial correlation coefficients removing the effect of sex were used to assess relationships between step and sprint velocity during the first four steps and a variety of variables. Significant (p = 0.05) correlations and partial correlations were found between overall sprinting velocity and subject height, countermovement jump, average horizontal force, vertical force, H:V force, stride frequency, foot contact duration and step distance. During the acceleration phase of sprint training, it may be important to liberalize step length after the first two steps. A variety of other recommendations are made.